THE ROLE OF MODERN MULTIMEDIA TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Juraeva Nargiza Oltinboevna; Kenjayeva O‘g‘iloy Raxmat qizi (Bright Mind Publishing, 2025)
This article describes the theoretical and practical bases of applying for the role and training of e-learning resources for use in classes.
Keywords: E-learning resources, modern information technologies, computer science, education, presentation, design, virtual education.